Trends in prevalence and implant types in the Nova Scotia Joint Database Registry between 2005 and 2021 - Rocio D. P. Pasache Lozano; Edwin A. Valencia Ramón; David G. Johnston; J. A. I. Trenholm (Bone & Joint Open, 2023)
Aims: The aim of this study is to evaluate the change in incidence rate of shoulder arthroplasty, indications, and surgeon volume trends associated with these procedures between January 2003 and April 2021 in the province of Nova Scotia, Canada. Methods: A total of 1,545 patients between 2005 and 2021 were analyzed. Patients operated on between 2003 and 2004 were excluded due to a lack of electronic records. Overall, 84.1% of the surgeries (n = 1,299) were performed by two fellowship-trained upper limb surgeons, with the remainder performed by one of the 14 orthopaedic surgeons working in the province. Results: Total shoulder arthroplasty (TSA) was the most frequent procedure (32.17%; n = 497), followed by stemmed hemiarthroplasty (SHA) (27.7%; n = 428). The most frequent indication for primary shoulder arthroplasty was degenerative osteoarthritis (58.1%; n = 882), followed by acute proximal humerus fracture in 15.11% (n = 245), and rotator cuff arthropathy in 14.18% (n = 220). The overall rate of revision was 7.7% (2.8% to 11.2%). The number of TSAs and reverse shoulder arthroplasties (RSAs) has been increasing since 2016. The amount of revision cases is proportional to the number of operations performed in the same year throughout the study period. Conclusion: The incidence of shoulder arthroplasty in the Maritime Provinces has increased over the last 16 years. Revision rates are similar the those found in other large database registries. Reverse shoulder arthroplasty prevalence has increased since 2016. Cite this article: Bone Jt Open 2023;4(8):567–572.